2013
DOI: 10.1002/etc.2170
|View full text |Cite
|
Sign up to set email alerts
|

Current‐use pesticides in stream water and suspended particles following runoff: Exposure, effects, and mitigation requirements

Abstract: The European Union's directive for sustainable use of pesticides requires implementing risk mitigation measures at streams threatened by pesticide entries. The need for mitigation measures was investigated at 10 stream sites within an intensively used arable region in central Germany by characterizing pesticide exposure following edge-of-field runoff and effects on the aquatic macroinvertebrates. Moreover, the influence of riparian buffer strip width (as a mitigation measure) at the sampling sites was consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 42 publications
6
38
1
1
Order By: Relevance
“…It follows that insecticides are an important threat to European freshwater biodiversity, as insecticide levels > RACs lead to severe biodiversity reductions (Stehle and Schulz 2015). This conclusion is in line with smaller-scale field studies reporting pesticide-induced adverse effects on ecosystem function and aquatic biodiversity in small agricultural surface waters (e.g., Schäfer et al 2012;Berenzen et al 2005;Bereswill et al 2013) and a study conducted on organic pollutants in larger EU surface waters (Malaj et al 2014). However, for the first time, the present meta-analysis uses empirical evidence based on scientific data and official RACs to illustrate the extent of the risk for European aquatic ecosystems.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…It follows that insecticides are an important threat to European freshwater biodiversity, as insecticide levels > RACs lead to severe biodiversity reductions (Stehle and Schulz 2015). This conclusion is in line with smaller-scale field studies reporting pesticide-induced adverse effects on ecosystem function and aquatic biodiversity in small agricultural surface waters (e.g., Schäfer et al 2012;Berenzen et al 2005;Bereswill et al 2013) and a study conducted on organic pollutants in larger EU surface waters (Malaj et al 2014). However, for the first time, the present meta-analysis uses empirical evidence based on scientific data and official RACs to illustrate the extent of the risk for European aquatic ecosystems.…”
Section: Discussionmentioning
confidence: 59%
“…In addition, several additional small-scale field studies conducted in the EU reported that pesticide exposure produced adverse effects on the aquatic ecosystem structure and function (e.g., Bereswill et al 2013;Schäfer et al 2012;Beketov et al 2013;Schulz 2004). However, no scientific study exists that has evaluated pesticide, or specifically insecticide, field concentrations in EU agricultural surface waters using the regulatory acceptable concentrations (RACs) defined by the environmental risk assessment conducted for official EU authorization.…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, this study proved that buffer strip widths were of limited importance for pesticide exposure levels in streams due to concentrated runoff entries via erosion rills, which prevented laminar sheet flow of runoff across the buffer. In addition, Bereswill et al (2013) showed for an intensively used arable agricultural region in central Germany with slopes varying between 1% and 3% that wide buffer strips do not protect surface waters from high pesticide concentrations due to the presence of erosion rills at the investigated sites.…”
Section: Introductionmentioning
confidence: 98%
“…More recently, Zubrod et al (2014) has provided evidence that single fungicides and fungicide mixtures result in sublethal and also lethal effects in amphipods at environmentally relevant concentrations. Moreover, they have suggested that when considering repeated exposure together with the presence of multiple stressors in the field, synergistic effects may appear (Holmstrup et al, 2010;Bereswill et al, 2013). Some of these fungicides, such as imazalil and tebuconazole, have been detected in the Júcar River.…”
Section: Discussionmentioning
confidence: 97%